Do We Eradicate Helicobacter pylori in Hospitalized Patients with Peptic Ulcer Disease? - Frank Wong; George Ou; Sigrid Svarta; Ricky Kwok; Kieran Donaldson; Joe Frenette; Robert Enns (Canadian Journal of Gastroenterology)
BACKGROUND: Helicobacter pylori infection is the most common chronic infection in humans. It is a major contributor to the cause of duodenal and gastric ulcers worldwide. Its eradication has been shown to reduce rates of H pylori-related ulcers as well as other complications such as gastric cancer.